2008
DOI: 10.1037/1099-9809.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative dissonance, ethnic identity, and youth violence.

Abstract: Studies suggest that the process of acculturation for immigrant youth, particularly for second-generation youth, is significantly associated with delinquency and violence. This study explored the acculturation-violence link with respect to acculturative dissonance and ethnic identity. The results revealed in a sample of 329 Chinese, Cambodian, Mien/Laotian, and Vietnamese youth that acculturative dissonance was significantly predictive of serious violence, with full mediation through peer delinquency. Ethnic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 59 publications
4
80
1
Order By: Relevance
“…An acculturation gap between parent and child has been associated with parenting difficulties and family conflict in Asian American families (Buki, Ma, Strom, & Strom, 2003;Lee et al, 2000), which in turn has been reported to mediate the effect of the acculturation gap on depressive symptoms in Asian American adolescents (Ying & Han, 2007). Acculturation gaps have also been reported to be predictive of youth violence (Le & Stockdale, 2008) and have also been hypothesized to play a role in the initiation of substance use in AAPI youth (Bhattacharya, 1998). In general, clinicians serving AAPI youth should assess acculturation, be alert to the possibility of acculturation gaps contributing to family conflicts, and understand how these cultural dynamics can affect the mental health and risk behaviors of these youth.…”
Section: Specific Cultural Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…An acculturation gap between parent and child has been associated with parenting difficulties and family conflict in Asian American families (Buki, Ma, Strom, & Strom, 2003;Lee et al, 2000), which in turn has been reported to mediate the effect of the acculturation gap on depressive symptoms in Asian American adolescents (Ying & Han, 2007). Acculturation gaps have also been reported to be predictive of youth violence (Le & Stockdale, 2008) and have also been hypothesized to play a role in the initiation of substance use in AAPI youth (Bhattacharya, 1998). In general, clinicians serving AAPI youth should assess acculturation, be alert to the possibility of acculturation gaps contributing to family conflicts, and understand how these cultural dynamics can affect the mental health and risk behaviors of these youth.…”
Section: Specific Cultural Issuesmentioning
confidence: 99%
“…Immigrant youth tend to adopt the values of the host countries more quickly than their parents do, resulting in discrepancies in values between the youth and their families (Chung, 2001;Phinney, Ong, & Madden, 2000). Emerging research supports strategies to reduce youth violence and substance abuse that include supporting positive ethnic identity development, enhancing bicultural self-efficacy (the ability to function effectively in multiple cultural contexts), and improving family communication by addressing intergenerational cultural conflicts (Le & Stockdale, 2008;Soriano, Rivera, Williams, Daley, & Reznik, 2004;Szapocznik, Prado, Burlew, Williams, & Santisteban, 2007).…”
Section: Ethnic Identity and Healthmentioning
confidence: 99%
“…Across age, generation, and ethnic group, subjective perceptions of acculturation gaps and acculturative dissonance are consistently associated with higher perceived family problems, such as less parenting satisfaction, less parent-child bonding, less family cohesion, and more family conflict, as well as youth maladjustment, such as substance use, conduct problems, and depression [Ahn, Kim, & Park, 2008;Asvat & Malcarne, 2008;Buki, Ma, Strom, & Strom, 2003;Choi, He, & Barachi, 2008;Feliz-Oritz, Fernandez, & Newcomb, 1998;Hwang & Wood, 2008;Le & Stockdale, 2008;Lee, Choe, & Ngo, 2000;Rosenthal, Ranieri, & Klimidis, 1996;Smokowski & Bacallao, 2006;Tsai-Chae & Nagata, 2008;Unger, Rita-Olson, Soto, & BaezcondeGarbanati, 2009;Ying & Han, 2007].…”
Section: Real Versus Perceived Acculturation Gapsmentioning
confidence: 99%
“…These cultural differences are thought to exacerbate normative intergenerational conflict. Acculturative dissonance involves conflicts that stem from differences in beliefs, values, and attitudes associated with immigration [Le & Stockdale, 2008]. Portes and Rumbaut [2001] note that 'dissonant acculturation takes place when children's learning of English and introjections of American cultural outlooks so exceed their parents' as to leave the latter hopelessly behind.…”
Section: The Acculturation Gap-distress Modelmentioning
confidence: 99%
“…The evidence indicates that immigrant adolescents generally have limited access to peers, less autonomy over friend selection, and engage in less informal socializing with peers, leading to their lower levels of exposure to criminogenic peer-based risks [70,71,74]. However, Dipietro and McGloin found that immigrant adolescents are more vulnerable than native-born youth when facing a similar level of exposure to peer delinquency [75].…”
Section: Empirical Evidence and Research Gapsmentioning
confidence: 96%